Evaluation of results of Total Elbow Arthroplasty with a Linked Semiconstrained Prosthesis - Saran, Rajat; Saxena, Anand (International Journal of Medical Research and Review, 2014)
Introduction: Extremity arthroplasties have been performed for 150 to 200 years, but no arthroplasty has been developed that universally meets the needs of every patient with a disabled elbow joint. Although the frequency of total elbow arthroplasty is much less as compared to hip and knee, it has definitely made an emphatic place for itself in the world of joint replacements. Methods: This is a study of nine patients out of eleven, as two patients were lost to follow up very early in the process. Between August 2004 to August 2014 nine patients were taken up for total elbow replacement for different indications which included neglected supracondylar fractures of the humerus sustained in childhood, rheumatoid arthritis and grossly comminuted fractures, closed and compound, of the distal humerus. Results: Out of the nine patients considered, seven had no pain whereas two patients with a comminuted compound fracture of the lower end of humerus, with one patient in whom myositis was excised, complained of regular pain postoperatively. Conclusion: The aim of this prospective study is to evaluate the results of the linked prosthesis in total elbow arthroplasty for different indications.